2021
DOI: 10.1080/0969594x.2021.1884042
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on factors influencing teachers’ intentions and implementations regarding formative assessment

Abstract: Teachers are playing crucial roles in the implementation of formative assessment, which has been widely recognised as a valuable strategy in enhancing students' learning outcomes. However, systematic analysis on factors that might facilitate or hinder teachers' intentions and implementations regarding formative assessment is scarce. This review covers 52 eligible studies and identifies factors, which have been categorised into personal and contextual factors, that influence teachers' intentions and implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 82 publications
(171 reference statements)
7
59
0
9
Order By: Relevance
“…The available literature has shown that student teachers respond to feedback in distinct ways within specific courses, curricula and contexts, depending on their previous experiences and their personal characteristics [21], and this was confirmed by our data as well. In fact, we have found the convergent and divergent perspectives offered by this research, including thoughts on the limitations of feedback, to be highly significant for developing insights about online feedback practices.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The available literature has shown that student teachers respond to feedback in distinct ways within specific courses, curricula and contexts, depending on their previous experiences and their personal characteristics [21], and this was confirmed by our data as well. In fact, we have found the convergent and divergent perspectives offered by this research, including thoughts on the limitations of feedback, to be highly significant for developing insights about online feedback practices.…”
Section: Discussionsupporting
confidence: 89%
“…An extensive body of research on assessment has long been highlighting the role of feedback in enhancing students' learning outcomes and in the development of selfregulation [14][15][16][17][18][19][20][21].…”
Section: Feedback Revisited Possibilities and Challenges In Digitally Mediated Educationmentioning
confidence: 99%
“…It was found that teachers should know about different ways of student assessment and use assessment in a way that helps learners in better learning. These findings are in agreement with (Al-Khairi, 2015;Al-Thumali, 2011;Barnes & Lock, 2013;Çelik et al, 2013;Khaksefidi, 2015;Soleimani & Zanganeh, 2014;Van Driel & Berry, 2012;Wei & Hui, 2019;Zamani & Ahangari, 2016;Yan et al, 2021). As it was found in this study, they believed that testing, scoring, assessing, and giving feedback are factors that help learners in better learning and effective teachers should know how to run them in their classroom.…”
Section: Qualitative Studysupporting
confidence: 88%
“…Their evaluation is another necessary mechanism to ensure the competence and conscientiousness of teachers. Also, in many English language programs, systematic evaluation of teachers is rare (Yan et al, 2021). It is common and irregular to be done by managers and senior teachers who do not have enough time and knowledge to do so, so teaching English according to many experts, there is an urgent need for community evaluation for teachers (Mazandarani & Troudi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Contextual factors play an important role in the implementation of formative assessment strategies in class (Yan and Cheng 2015). Yan et al (2021) conducted a systematic review on factors that affect teachers' intentions and implementation of formative assessment. They mention the importance of a positive school environment, strong internal school support, supportive working conditions and encouraging external policies.…”
Section: Implementing Scaffolding Strategiesmentioning
confidence: 99%